Design of circular flexible plates under of corrosion wear - Mavzovin Vladimir; Ovchinnikov Igor (E3S Web of Conferences, 2021)
The problems of optimal design of metal structures are usually formulated as the problem of finding such values of the selected parameters of structures that provide the smallest (or largest) value of the selected optimality criterion in the area of admissible design solutions. In most works on the optimization of metal structures, parametric problems are considered, limited by the preliminary assignment of a constructive form with the possibility of changing its parameters. To solve these problems, both deterministic and probabilistic optimization models can be used. A deterministic problem of optimal design of flexible round metal plates exposed to the combined action of a load and an aggressive environment causing corrosive wear of one of the plate surfaces is considered. A feature of the statement is that it takes into account the effect of the stressed state of the plates on the kinetics of their corrosive wear. Due to the insufficient efficiency of random search methods, the sequential quadratic programming technique is used. Two formulations of the optimal design problem are formulated, which are reduced to the minimax problem. 8 optimization projects were considered, their comparative analysis was carried out. It is shown that the realization of the found optimal thickness profiles leads either to a significant decrease in the stress level at the end of the plate’s service life, or to a significant increase in the service life. Calculation results show that maximum fatigue life designs are equal at end-of-life, and the maximum increase in fatigue life for hard- pinned inserts along the contour is 59%. As a result of the study, it was found that the problems of optimal design of flexible round plates under conditions of corrosive wear (the rate of which depends on the level of stresses in the plates), presented in the form of a minimax problem, can be effectively solved using the sequential quadratic programming technique, and the study of time evolution is intense -strain state can be carried out using a combination of the mesh method and the Adams method. Realization of the found optimal thickness profiles leads either to a significant decrease in the stress level at the end of the plate’s service life, or to a significant increase in the service life.